PROFITABILITY AND LIQUIDITY OF TRADING COMPANIES IN THE REPUBLIC OF SERBIA - Vlaović Begović, Sanja; Momčilović, Mirela (International Journal of Economic Practice and Policy, 2019)
Bearing in mind that the commercial sector is considered the most vital and the most resistant part of the economy, there was a need to examine the profitability of trading companies. The sample consists of 41 trading companies of medium and large size that operate in the Republic of Serbia. Analyzed companies are engaged in retail, wholesale and motor vehicles trade. The results of the research showed that the gross and net profit margins in the observed years are on average higher in the middle sized compared to large sized trading enterprises. Middle sized trading companies on average have rate of return on assets higher for approximetely 2% then large trading companies, while their rate of return on invested capital is on average higher for 8% to 10%. Average values ​​of net and gross profit margins are highest for companies that are engaged in trade of motor vehicles, and the lowest for retail companies. Wholesale companies and companies that are engaged in trade of motor vehicles are liquid, while retail companies are illiquid.
Keywords: analysis; Trading company; liquidity; Profitability